National climate policies in times of the European Union Emissions Trading System (EU ETS) - Johannes Burmeister; Sonja Peterson (Kiel Institute for the World Economy (IfW), 2016)
Given that the carbon price in the EU Emissions Trading System is only around 5 exteuro/tCO2 while consensus about a more stringent EU climate policy is very unlikely in the near future, we explore the potential scope and optimal design of additional national climate policies in the current EU policy framework. In particular, we suggest to implement a type of carbon price floor in the national EU ETS sectors that either allows for i) shifting emissions to non-ETS sectors like housing and transport or ii) retiring EU-wide emission allowances. In a simple theoretical framework with two countries and two sectors, we show that these two policy options are efficient up to a certain carbon price threshold. Moreover, efficiency is the highest at an optimal carbon price level equaling a weighted sum of the price differentials between ETS and non-ETS sectors. In order to determine the empirical relevance, we conduct a numerical partial equilibrium analysis of the EU carbon market in 2020. We find that Germany shows the highest potential to reduce EU-wide inefficiencies. With a price floor of 36 exteuro/tCO2 in 2020, Germany could reduce national climate policy costs by 13% if emissions are shifted from the ETS to non-ETS sectors. If they are willing to take on additional costs by retiring emission allowances, they are able to reduce EU ETS emissions by 1.6%.
Keywords: Q58; H21; H23; D58; 330; Climate policy; EU Emission Trading System; Overlapping regulation; Carbon price floors; Abatement costs